AN ANALYSIS OF GRAMMATICAL AND LEXICAL COHESION IN “Q1” ALBUM BY GAMALIEL - Dewi Lindasari; Amirudin Latif; Syaifudin Latif Darmawan (Journal of English Education and Enterpreneurship (JEEP), 2022)
Cohesion is the relation between one sentences and another sentence, it refers to the meaning in the sentence. Cohesion is divided into twotypes; grammatical cohesion and lexical cohesion. This research analyzegrammatical and lexical cohesion types in the song lyric of Q1 Album by Gamaliel.The objectives of this research were to identify the kinds of grammatical and lexicalcohesion found in the song lyric and to know the most dominant type found.Descriptive qualitative method was used to classify and analyze the data. Thisresearch applied the theory of Halliday and Hasan to identify the types ofgrammatical and lexical cohesion. The researcher found 217 cohesion items whichconsist of 181 references, 1 substitution, and 16 conjunction in grammaticalcohesion. While in lexical cohesion, there are 11 reiteration (9 repetitions, 1synonym, and 1 general word) and 8 collocations. The most dominant type ofgrammatical cohesion is personal reference with 121 items or around 55.7% andrepetition with 9 items or around 4.1% in lexical cohesion.